THE SOCIOLOGY OF CONSPIRACY THEORIES - Ganapathi H B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Conspiracy theories, often dismissed as fringe or irrational beliefs, hold significant sociological importance as reflections of broader societal anxieties, power dynamics, and cultural transformations. This paper explores conspiracy theories not merely as misinformation but as social phenomena deeply embedded in the structures of modern societies. It examines how conspiracy theories emerge in response to perceived inequalities, institutional mistrust, and the search for meaning in complex or uncertain circumstances. The sociology of conspiracy theories considers the role of social conditions—such as economic distress, political polarization, and media fragmentation—in facilitating the widespread acceptance of alternative narratives that challenge official accounts. Conspiracy theories are shown to thrive in environments marked by rapid change, declining trust in authorities, and the erosion of shared epistemologies. The paper also addresses the psychological underpinnings of conspiratorial thinking, such as cognitive biases and the desire for control, but situates these within collective experiences and social contexts. It analyzes how media, particularly digital and social platforms, serve as accelerators for the formation of conspiratorial communities and the circulation of unverified information. Conspiracy theories can serve both as forms of resistance and as tools of manipulation, used by political actors to mobilize support or discredit opponents. Their implications for democracy, social cohesion, and institutional legitimacy are profound, particularly in societies where pluralism and trust are already under strain. Rather than viewing conspiracy theories solely as a threat to rational discourse, this paper argues that they must be understood as meaningful social texts—expressions of grievances, fears, and contested knowledge. Through a sociological lens, conspiracy theories reveal the ways in which modern individuals and groups navigate uncertainty, power, and belonging in increasingly complex societies. By analyzing their origins, dissemination, and social functions, this study contributes to a deeper understanding of contemporary belief systems and collective behavior.